2023
DOI: 10.3390/membranes13050488
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Physical Properties of Electrospun Nanofiber Mats for Different Biomedical Applications

Abstract: Electrospun nanofiber mats are nowadays often used for biotechnological and biomedical applications, such as wound healing or tissue engineering. While most studies concentrate on their chemical and biochemical properties, the physical properties are often measured without long explanations regarding the chosen methods. Here, we give an overview of typical measurements of topological features such as porosity, pore size, fiber diameter and orientation, hydrophobic/hydrophilic properties and water uptake, mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 176 publications
0
9
0
Order By: Relevance
“…However, upon compositing 1% gelatin in the 5% PCL polymer solution, the fibers started to form without any bead formation, as shown in Figure B–E. The pore size of the nanofiber mats (from n = 3 same magnification FESEM images) has been measured by employing the long-axis measurement method using ImageJ software, a similar protocol reported in the previous literature. , It was observed that with increasing gelatin content in the nanofiber mats, the pore size of the nanofiber mats decreased significantly, as shown in Figure F. Static collector-derived 5% PCL nanofiber mat reported pore size of 1.143 ± 0.069 μm, while 5% PCL + 1% gelatin composite nanofiber mats reported pore size of 0.750 ± 0.033 μm and 5% PCL + 4% gelatin nanofiber mat reported pore size of 0.516 ± 0.040 μm.…”
Section: Resultsmentioning
confidence: 53%
“…However, upon compositing 1% gelatin in the 5% PCL polymer solution, the fibers started to form without any bead formation, as shown in Figure B–E. The pore size of the nanofiber mats (from n = 3 same magnification FESEM images) has been measured by employing the long-axis measurement method using ImageJ software, a similar protocol reported in the previous literature. , It was observed that with increasing gelatin content in the nanofiber mats, the pore size of the nanofiber mats decreased significantly, as shown in Figure F. Static collector-derived 5% PCL nanofiber mat reported pore size of 1.143 ± 0.069 μm, while 5% PCL + 1% gelatin composite nanofiber mats reported pore size of 0.750 ± 0.033 μm and 5% PCL + 4% gelatin nanofiber mat reported pore size of 0.516 ± 0.040 μm.…”
Section: Resultsmentioning
confidence: 53%
“…In this way, the program provides the area corresponding to the empty zones (porosity). Surface porosity was compare with a gravimetric method proposed by Safari et al [46,47]. To determine the weight of the enclosed water sample, the absorbed water at the sample surface was swiftly scraped using a paper filter and weighed to prevent evaporation.…”
Section: Pan Fibers Characterizationmentioning
confidence: 99%
“…5 Polycaprolactone-polytetrahydrofuran-polycaprolactone. 6 Polyethylene-co-vinyl acetate. 7 Polydimethylsiloxane.…”
Section: Solutions Using Block Copolymermentioning
confidence: 99%
“…Meanwhile, they are still imbued with the physical properties of the material from which they are built. These properties can help the materials to be applied in some applications that require a certain physical strength [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%